Exploration of the Clinical Parameters as Predictive Biomarkers and Their Potential Roles in the Regulation of Inflammation in Elderly Septic Patients with Pneumonia - Zhao J; Wang J; Wei B; Liu Y (Journal of Inflammation Research)
Jingjing Zhao,1 Junyu Wang,2,3 Bing Wei,2,3 Yugeng Liu1– 3 1Department of Infectious Disease and Clinical Microbiology, Beijing Chaoyang Hospital, Capital Medical University, Beijing, 100043, People’s Republic of China; 2Emergency Medicine Clinical Research Center, Beijing Chaoyang Hospital, Capital Medical University, Beijing, 100043, People’s Republic of China; 3Beijing Key Laboratory of Cardiopulmonary Cerebral Resuscitation, Clinical Center for Medicine in Acute Infection, Capital Medical University, Beijing, 100043, People’s Republic of ChinaCorrespondence: Bing Wei, Emergency Medicine Clinical Research Center, Beijing Chaoyang Hospital, Capital Medical University, 5 Jing-Yuan Road, Beijing, 100043, People’s Republic of China, Email dr_weibing@126.com Yugeng Liu, Emergency Medicine Clinical Research Center, Beijing Chaoyang Hospital, Capital Medical University, 5 Jing-Yuan Road, Beijing, 100043, People’s Republic of China, Email yugeng_liu@126.comBackground: The lack of knowledge on the characteristics, predictive values and potential roles of the clinical parameters for elderly septic patients with pneumonia hinders the application of precision medicine in sepsis and understanding of the possible mechanisms in the regulation of inflammation.Methods: This study retrospectively studied elderly patients with sepsis, who were admitted to the emergency department of Beijing Chaoyang Hospital between October 2021 and June 2022, according to the sepsis-3.0 diagnostic criteria. Patients were divided into subgroups based on the clinical outcome at the 28-day interval and occurrence of pneumonia. Baseline characteristic data and the routine laboratory test results were collected or recorded within 24 h after admission to the emergency department. Logistic regression analysis, receiver operating characteristic curve (ROC) analysis and Pearson correlation analysis were conducted.Results: In total, 138 elderly patients with sepsis were included in this study. Age, HGB, ALB, PCT/ALB ratio and PCT/CHOL ratio were risk factors associated with the occurrence of pneumonia in elderly patients with sepsis. The NEU/CHOL ratio possessed both diagnostic value in the survival group and prognostic value in the pneumonia group. Correlation analysis demonstrated characteristic links between HGB, ALB, lactate, NEU and lipids in different subgroups.Conclusion: Our study for the first time revealed that levels of HGB and ALB, along with the ratios of PCT/ALB, PCT/CHOL, and NEU/CHOL, can serve as potential diagnostic and prognostic markers for elderly septic patients with and without pneumonia. The link between these clinical parameters may provide insights into their potential roles in the regulation of inflammation in sepsis.Keywords: sepsis, HGB, ALB, lactate, lipids